2016
DOI: 10.12688/f1000research.7326.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding and Engineering Polyketide Synthesis

Abstract: Polyketides are a diverse group of natural products that form the basis of many important drugs. The engineering of the polyketide synthase (PKS) enzymes responsible for the formation of these compounds has long been considered to have great potential for producing new bioactive molecules. Recent advances in this field have contributed to the understanding of this powerful and complex enzymatic machinery, particularly with regard to domain activity and engineering, unique building block formation and incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…It is reported that structurally diverse polyketides compounds are made by type I modular polyketide synthases (PKSs) from simple metabolites such as propionyl-CoA, malonyl-CoA and methylmalonyl-CoA 50 . There are three types of PKSs (types I, II and III) and type I PKSs are typically found in fungi 51 . We also found a type I polyketide synthase in a well-defined gene cluster that displayed significantly upregulated expression in the FB of H. erinaceus .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that structurally diverse polyketides compounds are made by type I modular polyketide synthases (PKSs) from simple metabolites such as propionyl-CoA, malonyl-CoA and methylmalonyl-CoA 50 . There are three types of PKSs (types I, II and III) and type I PKSs are typically found in fungi 51 . We also found a type I polyketide synthase in a well-defined gene cluster that displayed significantly upregulated expression in the FB of H. erinaceus .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, filamentous fungi were numerous times demonstrated to be able to recognize and correctly splice introns from foreign fungal mRNA sequences, bypassing the necessity to purify and clone large introns-free cDNAs from NRP gene cluster (Lazarus et al, 2014;Unkles et al, 2014). Usually, the choice of a taxonomically closely-related host is preferable, since it generally exhibits a good compatibility regarding codon usage, thus facilitating translation (Zhang and Liu, 2016). Indeed, in native hosts, mRNA sequences harbour mainly preferred codons, interspersed with scarcer codons in specific zones, so as to slow down the ribosome and enable the pre-folding of the translated proteins (Ongley et al, 2013).…”
Section: Heterologous Host Choicementioning
confidence: 99%
“…A different approach to the whole domain swapping, aiming at the substitution of AT-substrate specificity, is the site-directed mutagenesis ( Figure 5 ). Recent advances in sequencing methodology, bioinformatics, structural and synthetic biology contributed to the identification of amino acid signatures of ATs and have a significant impact on the engineering of PKS assembly lines [ 49 , 61 , 74 , 106 , 113 , 138 , 143 , 144 , 148 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 ].…”
Section: Strategies Of Acyltransferase-based Polyketide Engineerinmentioning
confidence: 99%
“…erythraea and related polyketide pathways. Their modification by deletion of the native AT and integration of a foreign AT, often regarded as domain substitution or swapping, was described in Section 3.1 , as well as in diverse reports and reviews [ 48 , 49 , 50 , 65 , 138 , 142 , 143 , 144 , 167 , 168 , 177 , 178 , 179 , 180 , 181 , 182 ]. Here, we provide examples of cross-AT complementation, where the functionality of an AT-inactivated PKS (PKS module) was restored by an external heterologous AT protein (e.g., introduction of a heterologous AT into a mutant strain containing an AT-inactivated PKS).…”
Section: Strategies Of Acyltransferase-based Polyketide Engineerinmentioning
confidence: 99%